2020
DOI: 10.1002/hsr2.160
|View full text |Cite
|
Sign up to set email alerts
|

Describing adverse events in Swiss hospitalized oncology patients using the Global Trigger Tool

Abstract: Background and aimsThe occurrence rate of adverse events (AEs) related to care among hospitalized oncology patients in Switzerland remains unknown. The primary objective of this study was to describe, for the first time, the occurrence rate, type, severity of harm, and preventability of AEs related to care, reported in health records of hospitalized hematological and solid‐tumor cancer patients in three Swiss hospitals.MethodsUsing an adapted version of the validated Global Trigger Tool (GTT) from the Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…And in the 48 studies whose data allowed us to calculate percentages of admissions with one or more AEs, these ranged from 7% to 69%. AE preventability percentages, which 37 studies (69%) reported, ranged from 7% to 93%; however, four of these studies provided no relevant raw data [ 21 , 45 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And in the 48 studies whose data allowed us to calculate percentages of admissions with one or more AEs, these ranged from 7% to 69%. AE preventability percentages, which 37 studies (69%) reported, ranged from 7% to 93%; however, four of these studies provided no relevant raw data [ 21 , 45 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers use all six of these [ 17 , 18 ] while most use only those relevant to their setting [ 19 , 20 ]. Yet others either create additional modules (e.g., Oncology Module [ 21 , 22 ]) or develop modified versions tailored specifically to their patient and care settings [ 3 , 23 ]. While former versions diverge too importantly from the original GTT to label it as GTT, they are still considered as trigger tools (TTs).…”
Section: Introductionmentioning
confidence: 99%
“…There were 132 (33.1%) moderate, 128 (32.1%) severe, 64 (16.0%) life-threatening, 57 (14.3%) mild and 18 (4.5%) fatal AEs (Table 5). The incidence rate by severity grade is shown in [6][7][8][9][10][11][12][13][14] days). Of these readmissions, 58.6% were caused by infections as febrile neutropenia (42.7%) and sepsis (8.7%), while the main non-infectious causes of readmission were mucositis (8.7%), stroke (5.3%), vomiting (4.7%) and paralytic ileus (3.3%) (S5 Table ).…”
Section: Severitymentioning
confidence: 99%
“…An epidemiological description of AEs occurring in pediatric oncology care processes should include adverse drug events (ADEs), which are a common cause of hospitalization in children with neoplasms [9], as well as AEs related to medical procedures [2]. Moreover, an essential aspect is the determination of AEs preventability, as this informs about opportunities to improve patient safety in medical care processes [10,11]. Preventability implies that the methods to avoid harm are known or that the harm is related to errors in medical care [12], so not all adverse events are preventable [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, all of these modules are used [ 16 , 17 ], while most researchers use only those modules relevant to their clinical setting [ 18 , 19 ]. However, other users of the GTT methodology design additional modules (e.g., oncology module [ 20 , 21 ]) or create modified versions, tailored specifically to their clinical context [ 8 , 15 , 22 ]. While some versions diverge too much from the original GTT to label it as GTT, they are still considered as trigger tools (TTs).…”
Section: Introductionmentioning
confidence: 99%